2019
DOI: 10.1007/s00401-019-01958-5
|View full text |Cite
|
Sign up to set email alerts
|

Microglial nodules provide the environment for pathogenic T cells in human encephalitis

Abstract: Microglia nodule formation is a common feature in inflammatory brain diseases mediated by T lymphocytes such as viral and paraneoplastic encephalitis, multiple sclerosis, and Rasmussen encephalitis (RE). However, its role has not been fully understood yet. We hypothesized that, in RE, microglial nodules provide an environment for the initiation of the later dominating T-cell cytotoxicity. In RE stage 0, small primary microglia nodules could be identified in the absence of T cells. These primary nodules showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 54 publications
1
69
0
1
Order By: Relevance
“…A similar mechanism has recently been observed in Rasmussen's encephalitis, an inflammatory and immune mediated epilepsy, driven by MHC Class I restricted cytotoxic CD8 + T‐cells, which directly interact with neurons and astrocytes (Bauer, Gold, Adams, & Lassmann, ; Bien et al, ; Dauvilliers et al, ). The initial step in the development of lesions in this disease is the formation of microglia nodules with inflammasome activation, which precedes the CNS infiltration by T‐cells (Tröscher et al, ). Interestingly, such microglia nodules are also abundant in the normal appearing white matter adjacent to active lesions in MS (Michailidou et al, ; Peferoen et al, ; Singh et al, ; van der Valk & Amor, , Figure ).…”
Section: Microglia and Macrophages In Inflammatory Diseases In Humansmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar mechanism has recently been observed in Rasmussen's encephalitis, an inflammatory and immune mediated epilepsy, driven by MHC Class I restricted cytotoxic CD8 + T‐cells, which directly interact with neurons and astrocytes (Bauer, Gold, Adams, & Lassmann, ; Bien et al, ; Dauvilliers et al, ). The initial step in the development of lesions in this disease is the formation of microglia nodules with inflammasome activation, which precedes the CNS infiltration by T‐cells (Tröscher et al, ). Interestingly, such microglia nodules are also abundant in the normal appearing white matter adjacent to active lesions in MS (Michailidou et al, ; Peferoen et al, ; Singh et al, ; van der Valk & Amor, , Figure ).…”
Section: Microglia and Macrophages In Inflammatory Diseases In Humansmentioning
confidence: 99%
“… Note : The table compares the key features of inflammatory lesions in the central nervous system mediated by different T‐cell populations, B‐cells, and innate immunity in rodent models and humans, also describing the reaction patterns of microglia/macrophages and astrocytes. References 1: Ajami et al (), 2: Ben‐Nun, Wekerle, and Cohen (), Lassmann et al (), 4: Wolf et al (), 5: Blaabjerg et al (). 6: Mayo et al (), 7: Basso et al (). 8: Bradl and Lassmann (), 9: Linington, Bradl, Lassmann, Brunner, and Vass (), 10: Misu et al (), 11: Pohl et al, , 12: Storch et al (). 13: Bien et al (), 14: Cabarrocas, Bauer, Piaggio, Liblau, and Lassmann (), 15: Dauvilliers et al (), 16: Ji, Perchellet, and Goverman (), 17: Laukoter et al (), 18: Na et al (), 19: Saxena et al (), 20: Steinbach et al (), 21: Tröscher et al (). 22: Machado‐Santos et al (), 23: van Nierop et al (), 24: Zrzavy et al (). 25: Felts et al (), 26: Marik, Felts, Bauer, Lassmann, and Smith (), 27: Nau and Brück (2002). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Rasmussen encephalitis, microglial nodules have been associated with neuronal phagocytosis, following CD8 T cell-mediated brain neuron destruction (170). In human PCD, similar to Rasmussen encephalitis, IFNγ-mediated signaling (STAT1 phosphorylation) occurs in microglial cells, which can further amplify cytokine/chemokine release (143,170). Further investigation on the role of microglia as an amplifier of inflammation and an executor of neuronal death is needed in PCD.…”
Section: Overall Immunological Scenario For the Initiation And Develomentioning
confidence: 99%
“…Microglia exist, in the same way as astrocytes, in a continuum of activation states and can, therefore, be involved in both tissue injuries and repairs. On the one hand, it has been shown that microglia mediate synapse loss, neuronal loss, and memory impairment in Alzheimer's disease (overview in [49] and [50]); mediate dopaminergic injuries via the NF-κB signaling pathway in Parkinson's disease [51]; or provide an environment for the initiation of T-cell cytotoxicity in Rasmussen encephalitis [52]. On the other hand, microglia can equally mediate protective effects such as reducing spreading depolarization and calcium overload [53], eliminating neutrophil invasion in brain ischemia [54], promoting seizure-induced neurogenesis [55], or maintaining the vascular integrity under hypoxia conditions [56].…”
Section: General Aspects Of Ms Pathology and The Relevance Of Glial Cmentioning
confidence: 99%